2021
DOI: 10.31635/ccschem.020.202000588
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Promoted Amide Bond Formation via One-Pot Nitrone in Situ Formation/Rearrangement Cascade

Abstract: A green and sustainable synthetic strategy for amide bond formation utilizing a visible light-promoted nitrone formation/rearrangement cascade was developed. This method utilized visible light as the sole and clean energy source without the need for an exogenous photoredox catalyst or additive. Moreover, nitrones are generated in situ, bypassing the isolation process and producing only nitrogen gas as a byproduct. The synthetic value of this protocol has potential applications in the syntheses of amides contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 60 publications
0
29
0
1
Order By: Relevance
“…胺和羧酸的直接缩合是构建酰胺键最 直接的方法, 因为原料易得且价格低廉, 然而这种方法 需要使用化学计量的活化试剂, 原子经济性较差. 2020 年, 我们课题组 [41] 报道了可见光促进的芳基重氮酯 1 与 亚硝基芳烃 72 通过硝酮的原位产生/重排构建酰胺键的 方法(Scheme 20). 在可见光的照射下, 芳基重氮酯光解 产生游离态卡宾 2, 随后亚硝基芳烃通过其亲核的 N-中 心与卡宾反应生成两性离子中间体 75, 它将进一步转 化为更稳定的硝酮 73.…”
Section: 通过氮叶立德中间体unclassified
“…胺和羧酸的直接缩合是构建酰胺键最 直接的方法, 因为原料易得且价格低廉, 然而这种方法 需要使用化学计量的活化试剂, 原子经济性较差. 2020 年, 我们课题组 [41] 报道了可见光促进的芳基重氮酯 1 与 亚硝基芳烃 72 通过硝酮的原位产生/重排构建酰胺键的 方法(Scheme 20). 在可见光的照射下, 芳基重氮酯光解 产生游离态卡宾 2, 随后亚硝基芳烃通过其亲核的 N-中 心与卡宾反应生成两性离子中间体 75, 它将进一步转 化为更稳定的硝酮 73.…”
Section: 通过氮叶立德中间体unclassified
“…Despite these significant advances, radical perfluoroalkylation based on the interactions between reactive intermediates and perfluoroalkyl halides remains scarce. Recently, Jurberg and Davies, 49 Koenigs et al, [50][51][52][53][54] Zhou et al, 55 and others [56][57][58] have reported the use of low-energy blue light to liberate free carbenes from donor-acceptor diazo compounds. We wonder whether it is possible to generate R f radicals by forming a transient intermediate between perfluoroalkyl iodides and free carbene (either singlet or triplet), thus initiating the 1,3-ATRA addition of R f I to vinyldiazoacetates.…”
Section: Introductionmentioning
confidence: 99%
“…Using DCM as solvent, the corresponding nitrone 3aa can be isolated in 46% yield under blue light irradiation in 4 h (Table 1, entry 1). Note that, 3aa will rearrange to amide by prolonging the reaction time [39]. To further improve the reaction efficiency, other reaction paraments were systematically screened (Table 1, entries 2-5).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these elegant progresses, to the best of our knowledge, catalyst and additive-free synthesis of nitrones from nitrosoarenes has not yet been discovered. Our group recently found that photo-generated carbene species from diazoalkanes can be efficiently trapped by nitrosoarenes under sole blue LED irradiation [39], thus providing a novel and efficient route to amides under benign reaction conditions . Control experiments revealed that nitrones were generated as the key intermediates which rapidly rearranged to the corresponding amides under blue LED irradiation.…”
Section: Introductionmentioning
confidence: 99%